A pre-1947 Bengali language Muslim women's edited magazine/ ১৯৪৭ সালের পূর্ববর্তী বাংলা ভাষায় মুসলিম মহিলা সম্পাদিত পত্রিকা (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
Chapter-1Introduction: Muslim women edited before 1947 mentioned by name.  Although the name of two newspapers is found to be negligible, it has not been traced till the time of present research. On the other hand, there are about forty newspapers edited by Hindu women.Chapter -2Names of Muslim Women Edited Newspapers – Annesa, Barshwani, Begum, Bulbul.  Suniti, JagOran was seen but not found.Chapter-3Annesa: In 1928 AD,' Annesa’ was edited by Sophia Khatun B.A. Although the paper was run by husband instead of wife, but there is no way to deny that 'Annesa' has been established as Muslim women editor with Sophia Khatun in front. Not only that, He was a calligrapher.  Ahmed Rafiq writes that, in addition to logic, linguistic emotion is quite strong in Sophia's speech, as is the anti-colonialist sentiment.  There is room for more research to know the last word about him.  Sophia Khatun was never seen writing again. The magazine's subject matter was varied and fascinating. Socioeconomics, politics, and foreign psychological topics attracted discussion journals.Chapter- 4‘Varshvani’ Magazine: Manifestation of the Joint Heart of Husband and Wife.  From 1932-37, Jahanara Chowdhury and her husband Altaf Chowdhury had an intimate interest.  Apart from stories, essays, poems, various topics were published here. Rabindranath gave a letter to Jahanara Chowdhury.  Rabindranath writes in the letter that on that day I received the hand of all Bangladeshi girls from you, it touched my heart.Chapter -5Shamsunnahar Mahmud was the editor of ‘Bulbul’ patrika. Shamsunnahar's nephew Anwar Bahar, who was an indirect patron. Shamsunnahar who wrote the first authentic biography of Rokeya. In 1340, Nazrul Islam, Abdul Odud, Abdul Karim, Jasimuddin, Dr. Kudrat-i Khoda, along with Adela Khan, Abul Mansoor Ahmad, Mohammad Wazed Ali, and Shamsunnahar wrote the Baishakh-Shravan issue. Chapter-6Begum: First Sufia Kamal and later Naseeruddin's daughter Noorjahan were the editors of the newspaper.  If it was published in 1947, after 1947 it was not published from Calcutta, but from Dhaka. The name of the newspaper says that it is only for women. However, 'Begum' newspaper became important and in some cases the only news carrier in Bengali language.Chapter-7Conclusion: Among the women edited magazines, the above magazines which touch on Muslim women deserve the distinction of Bengali literature and language.
Keywords: Pre-1947; Muslim women; magazines; signifiers of social progress